Comparative analysis of Ukrainian and foreign banking applications - Lohachova, Y.O.; Yesina, M.V. (Radiotekhnika, 2024)
Mobile banking applications have been actively used in the financial sector for several years. Such applications significantly facilitate the use of banking services for their users. At the time of active digitalisation, the financial sector also needed reforms and active changes, that is why developers have been actively working on creating first home banking and then mobile banking applications since the end of the last century. Mobile banking applications have come a long way in evolution, so that users can now perform not only simple banking operations, but also many new additional functions making life easier. The development of the technologies used has also led to the emergence of new vulnerabilities, which required the improvement of security systems in such applications. The development path and experience of Ukrainian applications is somewhat different from that of foreign ones, but no less valuable. The development of foreign applications is more standardised and controlled by the government. Such solutions allow for better verification of compliance with security requirements. However, it should not be forgotten that mobile banking was created to facilitate financial transactions remotely, and therefore it should be easy to use by the average user. The article provides a comparative analysis of Ukrainian and foreign banking applications, including: Stanford FCU, Fideuram, N26, Banque populaire du nord, Sparkasse, Monobank, Privat24, Ukrsib-online, Oschadbank, and PUMB. The applications were compared by two groups of criteria, namely security and convenience criteria. The article focuses not only on the aspects in which Ukrainian applications should develop, but also on those in which they have an advantage over foreign apps.